Sistem E-Voting Menggunakan Metode Rapid Application Development (RAD) Pada Pemilihan Calon Ketua Osis Berbasis Web - Rani Puspita Sari; Agung Perdananto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Ikhlas Multiprogram Jawilan Vocational School is a formal education that always elects the student council chairman every year. The system currently used for selecting the student council president has problems in the preparation process, the election process and the calculation process, the preparation takes a lot of time, the voting process is queued and there are even some invalid votes, and the counting process is done one by one. As a result of these problems, the election process takes a long time, hindering the teaching and learning process. In addition, the calculations are inaccurate because there are many invalid votes. The system development method used in this research is the RAD method which starts from requirements planning, system design, and implementation. This research produces an application system for managing election data as well as real-time acquisition results, so that it can assist the process of selecting student council presidents at SMK Ikhlas Multiprogram Jawilan.